2021
DOI: 10.1097/md.0000000000026352
|View full text |Cite
|
Sign up to set email alerts
|

Treatments of unruptured brain arteriovenous malformations

Abstract: Background: The best therapeutic option for unruptured brain arteriovenous malformations (bAVMs) patients is disputed. Objective: To assess the occurrence of obliteration and complications of patients with unruptured bAVMs after various treatments. Methods: A systematic literature search was performed in PubMed, EMBASE, Web of Science, and so on to identify studies fulfilling predefined inclusion criteria. Baseline, treatment, and outcomes da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The consensus is that patients with high-risk features should undergo treatment if the risk profile is favorable. 9,21,22 Surgery is an option when the risk is acceptable. 23,24 Continued effort to advance surgical techniques has been made to increase safety and effectiveness in achieving obliteration.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The consensus is that patients with high-risk features should undergo treatment if the risk profile is favorable. 9,21,22 Surgery is an option when the risk is acceptable. 23,24 Continued effort to advance surgical techniques has been made to increase safety and effectiveness in achieving obliteration.…”
mentioning
confidence: 99%
“…Preoperative embolization has been a long-standing surgical adjunct with presumed advantage in mitigating high-risk features, reducing bleeding, and delineating lesion margin. 9,21,22,25 However, embolization risks include periprocedural bleeding, resulting in overall 16% morbidity, 2% to 4% mortality, and new neurological deficits up to 14%. 12,26 Therefore, physicians should meticulously weigh the risk and benefit of preoperative embolization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When each treatment modality is analyzed individually, Liu et al in a review of 28 studies with an aggregate 5852 patients demonstrated obliteration rates of 98% for microsurgery, 87% for embolization, and 68% for SRS. They also reported complications of 1% stroke or death for microsurgery, 4% for embolization, and 8% for SRS [ 21 ].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Microsurgery plays a major role in the immediate eradication with a good result in low-grade lesions, but it carries a high rate of morbidity in the high-grade ones. 1 Radiosurgery can be used in many lesions with a success rate. 2 it can be used alone or after surgery or after partial embolization.…”
Section: Introductionmentioning
confidence: 99%